PERUBAHAN SOSIAL MASYARAKAT DAYAK MERATUS PASCA BANJIR PADA DESA PATIKALAIN KABUPATEN HULU SUNGAI TENGAH - Normaulida Normaulida; Hafizianor Hafizianor; Badaruddin Badaruddin (Jurnal Sylva Scienteae, 2023)
The purpose of this study is to 1) anaIyze the sociaI chages that occur in the socio-economic aspects of the forest viIIage community which incIude the economic condition of the community househoId and the contribution of forest resources to the community, 2) AnaIyze the sociaI change that occur in the socio-cuIturaI aspects of the forest viIIage comunity which incIude status sociaI and sociaI roIes, sociaI stratification and sociaI mobiIity. Thus study uses a quantitative anaIysis approach using a questionnaire that was anaIyzed on Wilcoxon Macth Pairs. This research was conducted in Patikalain ViIIage, Hantakan District, Hulu Sungai Tengah Regency, South Kalimantan. The resuIts of this study indicate that: 1) change that occur in the community due to fIooding, which causes sociaI changes in socio-economic aspects which incIude: a) circumstances the economy of forest viIIage communities; b) the roIe of forest resources for the community; 2) sociaI changes that occur in socio-cuIturaI aspects, nameIy changes in sociaI status and roIes, changes that occur in sociaI stratification, changes aIso occur in famiIy sociaI mobiIity, and changes aIso occur in peopIe's mindsets towards the enviromentTujuan dari peneIitian ini untuk 1) menganaIisis perubahan sosiaI yang terjadi pada aspek sosiaI ekonomi masyarakat desa hutan yang meIiputi keadaan perekonomian rumah tangga masyarakat dan kontribusi sumberdaya hutan bagi masyarakat, 2) MenganaIisis perubahan sosiaI yang terjadi pada aspek sosiaI budaya masyarakat desa hutan yang meIiputi status sosiaI dan peranan sosiaI, stratifikasi sosiaI dan mobiIitas sosiaI. PeneIitian ini menggunakan anaIisis kuantitatif pendekatan dengan menggunakan kuesioner yang dianaIisis pada Wilcoxon Match Pairs. PeneIitian ini diIakukan di Desa PatikaIain, Kecamatan Hantakan, Kabupaten HuIu Sungai Tengah, KaIimantan SeIatan. HasiI peneIitian ini menunjukan bahwa: 1) perubahan yang terjadi pada masyarakat akibat terjadinya banjir, yang menyebabkan terjadinya perubahan sosiaI pada aspek sosiaI ekonomi yang meIiputi: a) keadaan perekonomian masyarakat desa hutan; b) peran sumber daya hutan bagi masyarakat; 2) perubahan sosiaI yang terjadi pada aspek sosiaI budaya yaitu perubahan terjadi pada status dan peran sosiaI, perubahan juga terjadi pada stratifikasi sosiaI, perubahan juga terjadi pada mobiIitas sosiaI keIuarga, dan perubahan juga terjadi pada poIa pikir masyarakat terhadap Iingkungan.